Svanibor Pettan: an Appreciation - Jeff Todd Titon (Muzikološki Zbornik, 2019)
Svanibor Pettan is that rare kind of gentleman who immediately puts his acquaintances at ease and encourages them to feel as if they'd known him for a long time. These qualities have enabled him to succeed in helping to make the world a better place through music, and in helping his colleagues in Europe and abroad to mobilize around the field of applied ethnomusicology. For Svanibor, this has meant taking ethnomusicology beyond mere scholarship – that is, beyond the accumulation of knowledge and its dissemination within the community of scholars – to the application of that ethnomusicological knowledge in service to a deliberate intervention into the ethnic groups under study, to resolve conflicts that may lead to violence and instead to promote peace among them.